Pengawasan terhadap Praktik Money Game dengan Skema Ponzi di Platform TikTok Ditinjau dari Undang-Undang Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan - Moch Naufall Nurfauzan Akmal; Jejen Hendar (UNISBA Press, 2024)
Abstract. . A Ponzi scheme is an investment method using a pyramid model where profits paid to investors come from their own money or funds from newly recruited members. The allure of Ponzi schemes lies in the promise of high returns and simplicity. This journal aims to examine the supervision and legal consequences for individuals involved in illegal investments with Ponzi schemes in Indonesia. The goal is to provide the public with information on how illegal Ponzi scheme investments are supervised under Law Number 21 of 2011 concerning the Financial Services Authority (OJK) and other regulations. The research method used is normative legal research with a conceptual statutory approach, collecting legal materials from primary, secondary, and tertiary sources. The analysis technique is descriptive qualitative. The study reveals that the OJK has undertaken various surveillance efforts on illegal Ponzi scheme investments, including establishing an investment alert task force and implementing preventive and repressive strategies. However, these supervisory actions have not fully addressed illegal Ponzi scheme investments, as the term